Influência do hipotireoidismo sobre as alterações nociceptivas e morfológicas periféricas e centrais na neuralgia trigeminal em ratos - Silveira, Helson Freitas (2017)
Thyroid hormones (HTs) are important mediators of the growth and development of the organism, mainly of the CNS. The lack of HTs decreases neuronal volume, and causes defects in myelination. Hypothyroidism depresses neuronal excitability when associated with chronic peripheral lesion in rats, reduces conduction velocity, with absence of sensory potentials. Considering that hypothyroidism causes changes in the development of the neuronal response, with an increase in the excitability threshold of the peripheral nerve fiber. We investigated and evaluated peripheral and central nociceptive and morphological effects of hypothyroidism in the presence of neuropathic pain. Male Wistar rats, 180 to 220 g, maintained at 24 ° C, day / night cycle - 12/12 h, water ad libitum, free access to balanced feed, housed in groups of 4 per cage were used. The animals were divided into 6 groups of 6 animals: control (C), trigeminal neuralgia (NT), NT Sham, hypothyroidism (H), H + NT, H + NT Sham. Hypothyroidism was induced with 0.05% propylthiuracil (PTU) for 21 days, and confirmed by T4 dosing. Induction of trigeminal neuralgia was performed through infraorbital nerve constriction. The nociceptive threshold was measured by electronic Von Frey test 2 times a week after surgery for 21 days. The caudal trigeminal subnucleus (SCT), trigeminal ganglion (GT), infraorbital nerve (NIO), thyroid and vibrissa skin were collected. Immunofluorescence-labeled material with antibodies, anti-NeuN, anti-c-Fos, anti-PBM, anti-ATF-3 and anti-PGP 9.5 to evidence signs of cellular injury, pain and the integrity of nerve fibers. Thyroid stained in HE for histopathological analysis. Statistical analysis was done by mean ± SEM of the measurements recorded, data normalization by Shapiro-Wilk, analysis of variance (ANOVA one way or two way), with post- test of Turkey or Games-Howell determined by the test of homogeneity of variance of Levene, where values of p <0.05 were considered statistically significant and Spearman's correlation test. Our results showed a reduction in T4 levels, weight loss, increase in thyroid gland size and weight, follicular hyperplasia and thyroid hypertrophy, and negative correlation between T4 levels and thyroid morphometry. There was a reduction in the nociceptive threshold in the NT, but in the H group they showed an increase in the threshold and the threshold of the H + NT group showed at the control levels, suggesting a subclinical manifestation, in addition to a negative correlation with the T4 levels. ATF3 was shown to be elevated in neuropathic groups in GT, but did not express in SCT. C-Fos was elevated in the NT group, reduced in the H + NT in GT, but in the TE the c-Fos in the H + NT group rose above the NT group, which was also increased. PBM and DAPI were increased in the neuropathic groups, there were signs of axonal death and delamination of the myelin sheath. PGP 9.5 showed a decrease in the number of nerve endings in the skin of vibrissae in NT groups. We conclude that the induction model of hypothyroidism with PTU in rats is effective, reproduces the alterations found in humans with hypothyroidism, demonstrated through serological, behavioral, anatomopathological and histopathological studies. There is a negative correlation between T4 levels and thyroid morphometry. Hypothyroidism leads to disturbances in the nociceptive response in rats, and leading the pain signals in neuropathic state to subclinical levels. There is a negative correlation between T4 levels and the nociceptive threshold. The expression of c-Fos reduction in the trigeminal ganglion evidences the predominance of the peripheral effect in the nociception of hypothyroidism. Expression of ATF3 shows that hypothyroidism does not influence the ability of the peripheral neuron to initiate a response. Hypothyroidism decreases axonal repair ability and remyelination of peripheral pathways by reducing the amount of fibers and nerve endings shown in the expression of PBM and PGP 9.5.